Arka Muthu: new dwarf watermelon variety - Pitchaimuthu, M; Swamy, K R M; Rao, Sreenivasa; Hebbar, Shankara (Indian Horticulture, 2018)
Arka Muthu, a dwarf watermelon variety, has been developed by ICAR-IIHR,Bengaluru, through single plant selection from seeds collected from Attur, TamilNadu. It is evolved for its dwarf, bushy and compact vine with small, round fruitsof ice-box type. The flesh of fruits is very sweet (TSS, 12-14% Brix). It is an earlymaturingtype. Its dwarf plant stature makes its suitable for small garden asboth vines and fruits need little space. It is also suitable for high-density plantingsystem. This ice box watermelon is small enough to fit into refrigerator.